Impacts of temperature, relative humidity and total number of fruits on cucurbit fruit fly infestations under field condition (Progressive Agriculture, 2015)
The research was carried out in the field laboratory of the Department of Entomology, Bangladesh Agricultural University during April to July 2013 to correlate the temperature, relative humidity and number of fruits with the level of fruit infestations by cucurbit fruit fly, Bactrocerea cucubitae. Three cucurbitaceous vegetables namely bitter gourd (BARI Karola-1), ridge gourd (BARI Jhinga-1), and snake gourd (Local Chichinga) were taken as host crops. Percent fruit infestations were compared with the natural variation of temperature, relative humidity and number of fruits under field condition. Fruit infestations varied significantly with the variation of temperature, relative humidity and total number of fruits among three selected vegetables. Increasing of temperature had profound positive role in bitter gourd fruit infestation whereas negative relationship was found for ridge gourd infestation. However, statistically insignificant but positive effect of temperature was observed in snake gourd infestation. Fruit infestation of ridge gourd and snake gourd increased with the increase of relative humidity while negative relationship was observed in case of bitter gourd. Percent fruit infestations by cucurbit fruit fly were also found to be affected by total number of fruits. Positive but weak relationships were found between percent fruit infestations and total number of fruits of all three vegetables used in the experiments.Progressive Agriculture 26:1-5, 2015